IDENTIFKASI KERUSAKAN LAHAN HUTAN AKIBAT AKTIVITAS PERTAMBANGAN EMAS DESA BOWONE KECAMATAN TABUKAN SELATAN TENGAH - Cristina Pangemanan; Xaverius Erick Lobja; Cahyado Nugroho (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2022)
The problem of this research is changes in forest land use and the level of damage to forest land due to gold mining activities in Bowone Village, South Central Tabukan District, Sangihe Islands Regency. The research method is quantitative with GIS-based spatial analysis using Supervised Classification and NDVI. The study results show that the mining area expanded from 11.83 hectares in 2015 from 2.35 hectares to 14.18 hectares in 2020, with an average expansion of 2.37 hectares per year or 45.53% per year. Heavy damage in the forest area of ​​Bowone Village with an area of ​​131.2422 hectares (15%). Moderate damage with an area of ​​279,8941 hectares (35%), and light damage with an area of ​​435,7669 hectares (51.45). The condition of forest land cover in Bowone village is categorized as quite reasonable. However, it should be noted and anticipated that the current state of vegetation cover may decrease because 279.8941 hectares (33.05) have experienced a medium density category.